Insights into the Structural Basis of Antibody Affinity Maturation from Next-Generation Sequencing - Mishra, Arjun K.; Mariuzza, Roy A. (Frontiers in Immunology, 2018)
Affinity maturation is the process whereby the immune system generates antibodies of higher affinities during a response to antigen. It is unique in being the only evolutionary mechanism known to operate on a molecule in an organism’s own body. Deciphering the structural mechanisms through which somatic mutations in antibody genes increase affinity is critical to understanding the evolution of immune repertoires. Next-generation sequencing (NGS) has allowed the reconstruction of antibody clonal lineages in response to viral pathogens, such as HIV-1, which was not possible in earlier studies of affinity maturation. Crystal structures of antibodies from these lineages bound to their target antigens have revealed, at the atomic level, how antibodies evolve to penetrate the glycan shield of envelope glycoproteins, and how viruses in turn evolve to escape neutralization. Collectively, structural studies of affinity maturation have shown that increased antibody affinity can arise from any one or any combination of multiple diverse mechanisms, including improved shape complementarity at the interface with antigen, increased buried surface area upon complex formation, additional interfacial polar or hydrophobic interactions, and preorganization or rigidification of the antigen-binding site.